2023
DOI: 10.3390/nu15204406
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Data-Driven Dietary Patterns and Lung Cancer Risk: A Systematic Review and Dose–Response Meta-Analysis

Roberto Fabiani,
Gianandrea La Porta,
Laura Li Cavoli
et al.

Abstract: The effect of dietary patterns on lung cancer risk is currently debated. In this study, we evaluated the association between different “a posteriori” dietary patterns and lung cancer risk. The search was carried out (February 2023) through Scopus, Web of Science, and PubMed databases. Meta-analysis was performed by a random-effects model using risk values (RR and OR) extracted from the 12 selected studies. Two main dietary patterns were identified and named “Western/meat” and “Healthy/prudent”. The highest adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 57 publications
(198 reference statements)
0
6
0
Order By: Relevance
“…A comprehensive analysis of studies revealed no link between offal intake and lung cancer risk in nonsmokers; however, heavy smokers enrolled in a lung cancer screening program in Italy exhibited an elevated risk of lung cancer associated with increased offal consumption. [1,11] Earlier investigations have demonstrated a heightened risk of lung cancer -up to a 12% increase -linked to greater consumption of red meat and processed meat, even among nonsmokers (in the case of red meat) [8,11,15,18]. In contrast, no association was identified in the EPIC and NCS study.…”
Section: Offal Red Meat and Processed Meatmentioning
confidence: 92%
See 4 more Smart Citations
“…A comprehensive analysis of studies revealed no link between offal intake and lung cancer risk in nonsmokers; however, heavy smokers enrolled in a lung cancer screening program in Italy exhibited an elevated risk of lung cancer associated with increased offal consumption. [1,11] Earlier investigations have demonstrated a heightened risk of lung cancer -up to a 12% increase -linked to greater consumption of red meat and processed meat, even among nonsmokers (in the case of red meat) [8,11,15,18]. In contrast, no association was identified in the EPIC and NCS study.…”
Section: Offal Red Meat and Processed Meatmentioning
confidence: 92%
“…[1,4,6,10] Further analyses indicated that individuals with the highest intake of citrus fruit, compared to the lowest intake, experienced a 9% reduction in lung cancer risk [odds ratio 0.91 (95% CI 0.84-0.98)]. [7,8,10] In a cohort study comprising 34,198 participants, it was observed that the consumption of dried fruit three or more times per week was linked to a reduced risk of lung cancer, with a relative risk of 0.89. [11] Vegetables For current smokers, the intake of vegetables showed a significant association with a reduced risk of lung cancer (summary RR = 87%; 95% confidence interval: 0.78, 0.94), while no such association was observed for former smokers and never smokers.…”
Section: Fibre Fruit and Vitamin Cmentioning
confidence: 99%
See 3 more Smart Citations